The presence of the “internationality” of international criminal justice - Heyong, Wang (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
Justice is a perpetual topic for mankind. International criminal justice is generally regarded as criminal justice or global justice in academia, but neither of them can provide comprehensive content for international criminal justice alone. In order to make international criminal justice be correctly understood, both theories must be integrated. But there is tension between the two propositions. In order to bridge the gap between the two theories, it is necessary to build a bridge for the integration of the two theories ― international criminal justice must incorporate the “international” element. “Internationality” is an indispensable element of international criminal justice. Through the historical investigation of the concepts of “global justice” and “criminal justice”, this paper believes that the International Criminal Court must fully consider the “international” characteristics of “individual” embedded in “state” when allocating “negative evaluation” between different cases. The authority of the International Criminal Court can be maintained only when the “internationality” of international criminal justice is fully considered by the International Criminal Court.
Халықаралық қылмыстық сот төрелігінің «интернационалдылығының» болуы
Наличие «интернациональности» международного уголовного правосудия
Keywords: criminal justice; global justice; internationality; distributive justice; ICC; social contract; constitutional power; individual